Visual improvement following continuous positive airway pressure therapy in diabetic subjects with clinically significant macular oedema and obstructive sleep apnoea: proof of principle study. - Mason, R; Kiire, C; Groves, D; Lipinski, H; Jaycock, A; Winter, B; Smith, L; Bolton, A; Rahman, N; Swaminathan, R; Chong, V; Stradling, JR (2012)
BACKGROUND: Diabetic retinopathy and diabetic macular oedema are more prevalent in patients with coexistent obstructive sleep apnoea (OSA). OBJECTIVES: We assessed if treatment of OSA with continuous positive airway pressure (CPAP) might improve visual acuity (VA). METHODS: A total of 35 patients with clinically significant macular oedema (CSMO) and OSA [oxygen desaturation index (ODI) ≥10 or apnoea-hypopnoea index (AHI) ≥15] were identified and agreed to be studied. VA (expressed as the logarithm of the minimum angle of resolution, logMAR), macular thickness, fundal photographs, glycosylated haemoglobin (HbA1c) and rhodopsin mRNA were measured twice at baseline and at 3 and 6 months post-CPAP. Fluorescein angiography and the Epworth Sleepiness Scale (ESS) were obtained once at baseline and at 6 months. RESULTS: Three patients withdrew before the first trial visit. Thus, a total of 32 patients (17 males) entered the study, and 4 subsequently withdrew; thus 28 completed 6 months of follow-up. Baseline characteristics of the subjects were as follows [mean (SD or inter-quartile range)]: age 66.2 (7.1) years, body mass index 31.7 (6.3), HbA1c 7.4% (1.44) [57.1 (15.7) mmol/mol], AHI 16.5 (11-25), ODI 16.0 (12-25), ESS 6.5 (4.0-12.0) and duration of diabetes 9.5 years (5.0-16.5). Participants were divided into 13 high and 15 low CPAP compliers (≥ and <2.5 h/night over the 6 months, respectively). At 6 months, the adjusted treatment effect on VA of high compliance versus low compliance was 0.11 (95% confidence interval 0.21 to -0.002; p = 0.047), equivalent to a one-line improvement on the logMAR chart. There was no significant improvement in macular oedema or fundal photographs. CONCLUSIONS: This hypothesis-generating, uncontrolled study suggests that ≥2.5 h/night CPAP usage over 6 months in individuals with CSMO and OSA may be associated with improvement in VA. This provides justification for a randomised controlled trial of CPAP therapy in such patients.